“Career festival: My dream job", career introduction to primary school graders in Malang - Tri Muji Ingarianti; Nida Hasanati; I. Istiqomah; May Lia Elfina; D. Djudiyah; M. Shohib (Journal of Community Service and Empowerment, 2022)
SD Negeri 1 Jambesari is one of the elementary schools which has 119 students ranging from grade 1 to grade 6. Based on interviews, observations, and dialogue with teachers at SDN Jambesari 1, several problems were found related to students' lack of information on careers or professions. This activity aims to empower the community through a career introduction program that is carried out at SD Negeri 1 Jambesari. The methods used by the team are preparation, program planning, and program implementation. The implementation of career introduction is carried out through an informative and demonstrative profession by the project team, so that it becomes the result of this program. As a result, students are better able to explain a number of professions that they did not know before. Also, students have real-life experience through observing and demonstrating the tools of each profession. This community service has succeeded in increasing the cognitive aspects of students in recognizing various kinds of careers or professions, so that they can visualize their dream job in the future.